Complications And Revision Surgeries Associated With Single Bone Forearm Reconstruction - Ashok, Ashok; Narayan, Vikrant; Choudhary, Crazy; Meena, D S (Journal of Neonatal Surgery, 2025)
Background: Single bone forearm reconstruction is a surgical technique used to manage severe forearm bone defects. Despite its efficacy in restoring limb stability and function, the procedure is associated with notable complications and the potential need for revision surgeries. Methods: This retrospective study analyzed 30 patients who underwent single bone forearm reconstruction, focusing on complications, revision surgeries, and long-term outcomes. Data were collected on union rates, complication types, and patient satisfaction levels post-surgery. Results: The study found that 80% of patients achieved bone union without grafts, while 20% required additional interventions. Complications were reported in 6.67% of the cases, including volar subluxation of the wrist and skin flap necrosis. Overall, 93.33% of patients were satisfied with their surgical outcomes. Conclusion: Single bone forearm reconstruction provides effective management for severe forearm defects but carries a significant risk of complications and the need for potential revision surgeries. Ongoing monitoring and comprehensive postoperative care are essential to maximize patient outcomes and satisfaction.